Lectio praecursoria: The Good Noblemen Who Conquered the Kingdom: Islam, Historiography, and Aristocratic Legitimation in Late-Medieval Portugal - Queimada e Silva Tiago (Glossa ry, 2025)
This text consists of the 'lectio praecursoria' given at the defense of my doctoral dissertation "The Good Noblemen Who Conquered the Kingdom:  Islam, Historiography, and Aristocratic Legitimation in Late-Medieval Portugal". This dissertation deals with aristocratic historiography and political legitimation in late-medieval Portugal (late thirteenth and fourteenth centuries). It offers a perspective into the historical imaginary of the late-medieval Portuguese aristocracy; an imaginary that underlay the argumentation of members of this social class in defence of their traditional rights and jurisdictions against political
centralisation. It examines how the medieval Portuguese aristocracy utilized memories of past interactions with Islam to justify its privileged social status and defend its traditional prerogatives at a time when this social group opposed the royalist policy of political centralization. This research is included into wider debates on the role of culture — in this case, historical culture — as a resource to justify, reinforce, reproduce, and transform an existing social order.